2020
DOI: 10.1002/hed.26442
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness analysis of using the heat and moisture exchangers compared with alternative stoma covers in laryngectomy rehabilitation:USperspective

Abstract: Background: This study aims to evaluate the cost-effectiveness of using heat and moisture exchangers (HMEs) vs alternative stoma covers (ASCs) following laryngectomy in the United States. Methods: A cost-effectiveness and budget impact analysis were conducted including uncertainty analyses using real-world survey data with pulmonary events and productivity loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…36-42 Nevertheless, patients with COPD experience pulmonary symptoms similar to those of patients after laryngectomy, 43-46 and COPD is a common comorbidity for them. 47,48…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36-42 Nevertheless, patients with COPD experience pulmonary symptoms similar to those of patients after laryngectomy, 43-46 and COPD is a common comorbidity for them. 47,48…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39][40][41][42] Nevertheless, patients with COPD experience pulmonary symptoms similar to those of patients after laryngectomy, [43][44][45][46] and COPD is a common comorbidity for them. 47,48 Although no normative data are currently available for patients with total laryngectomy, the extent of improvement obtained in each of the 4 domains is most likely clinically significant. Indeed, a published work on patients with COPD concluded that improvements of 10.6 for cough symptom, 10.1 for cough impact, 9.5 for sputum symptom, and 7.8 for sputum impact were clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For those unable to meet the additional costs, or for those who may find using multiple devices too complex or cognitively demanding, the data from Phase 1 of this study demonstrates that simply exchanging the patients baseline HMEs with comparable HMEs from the new generation range can still achieve some incremental positive pulmonary and other symptom benefits. Prior studies have proven HMEs to be cost‐effective 10,27 . A full assessment of the incremental cost‐effectiveness of the change in routine using Provox Life is planned to investigate if the added 0.8 HME utilization can be justified by improvements in clinical outcomes and any impacts to quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Recognizing the negative consequences of total laryngectomy on pulmonary function, the use of heat and moisture exchanger (HME) devices are considered best practice care for pulmonary rehabilitation postsurgery. 1,[9][10][11] Attached over the tracheostoma, HMEs typically consist of a plastic housing containing polyurethane foam treated with a hygroscopic salt (e.g., calcium chloride, lithium chloride) to enhance absorption of water vapor and warmth upon inhalation. 1,12 Inhaled air passing through the warm, moist foam of the HME is conditioned and some particulate matter is filtered.…”
Section: Introductionmentioning
confidence: 99%